Moderating effect of IFRS on ownership-structures–audit-quality relationship for listed firms in Saudi Arabia - Fallatah, Emad Mohammed; Mohd Saat, Nur Ashikin; Mohammed Shah, Sabarina; Choo, Wei Chong (Society of Business and Management, 2021)
This research investigates the moderating effect of the IFRS adoption on the link between ownership structures and audit quality for listed non- financial firms in Saudi Arabia .Data were collected from 165 listed non-financial firms in Saudi Arabia over six-year periods that represent the pre-IFRS adoption period of 2013 to 2015 and post-IFRS adoption period of 2016 to 2018. Managerial ownership and concentrated ownership were interacted with IFRS adoption for discretionary accruals, a proxy of audit quality, factoring in instrumental variables in the constructs. Dynamic panel model estimation utilizing the two-stage generalized moment method (2 SGMM) was used to analyze the data because of its efficacy in mitigating possible endogeneity problems. The study’s findings reveal that ownership structure weakens audit quality in the pre IFRS adoption period and that the interaction effect of IFRS with ownership structure leads to high audit quality for listed non-financial firms in Saudi Arabia post-IFRS adoption period. The study concludes that firms’ convergence with IFRS for reporting purposes provides better audit quality through the instrumentality of ownership structures. The study recommends that, for companies under managerial ownership, the Capital Market Authority of Saudi Arabia should create rules that allow managers to have a maximum defined percentage of ownership stake. If enshrined in the Saudi Arabian corporate governance code of best practices for firms, this will lead to a reduction in the incidence of opportunistic managerial behavior. The findings of this study suggest that the decision of adopting the IFRS carries multiple consequences on ownership structures of firms and should always be considered by regulators in Saudi Arabia and other emerging markets in order to reach a reasonable audit quality level. Emerging markets that have adopted the IFRS like Saudi Arabia, as well as those that are planning to adopt it, should, therefore, consider the potential changes of the right shares of managers and owners as an indication of audit quality level.